Evaluation of the effect of probiotics on vaginal health: a integrative review (Revista Científica Integrada, 2023)
Aim: to evaluate the effect of using probiotics on vaginal health based on scientific evidence. Methods: integrative review, carried out in three databases. The terms used in the crossings were “Probiotics”, “Vagina” and “Treatment”. Among the eligibility criteria, the studies should have been published between 2013 and 2023, only with women over 18 years of age, who had not had a hysterectomy, and who were not undergoing treatment for cancer. Reviews, case studies, experience reports, and documents that were not articles, among others, were excluded. The use of probiotics was considered orally or topically, alone or combined. Results: In total, 22 studies were included in the final sample. Almost all results (81.8%) indicated that probiotics have some significant effect on improving the vaginal microbiota and reducing infections in the female genital tract. Conclusion: probiotics have a beneficial effect on vaginal health, they can reduce the appearance of conditions such as vulvovaginitis, and if associated with antimicrobial regimens, they enhance the chances of cure. Despite the findings, further clarification is still needed about the dose response and cost-effectiveness of these interventions.
Keywords: Probiotics; Vagina; Vaginosis, Bacterial; Treatment